The Role of Physical Activity and Sedentary Behavior on VO₂max as an Indicator of Cardiorespiratory Fitness: A Literature Review: Ramadhana Komala, Wiwi Febriani - Ramadhana Komala (Jurnal Kedokteran Universitas Lampung, 2026)
VO₂max is the primary indicator of cardiorespiratory fitness, reflecting the body's maximal capacity to uptake, transport, and utilize oxygen during physical activity. Physical activity and sedentary behavior are two important behavioral factors that influence VO₂max and cardiorespiratory fitness levels. This literature review aimed to examine the role of physical activity and sedentary behavior on VO₂max based on studies published over the last decade. The findings indicate that regular physical activity, particularly moderate-to-vigorous aerobic exercise, improves VO₂max through physiological adaptations in the cardiovascular, respiratory, and skeletal muscle systems. In contrast, high levels of sedentary behavior are associated with reduced aerobic capacity due to decreased muscular metabolic activity, impaired cardiovascular function, and an increased risk of metabolic disorders. Numerous studies have reported that individuals with higher levels of physical activity tend to have greater VO₂max values than those who are less active, whereas prolonged sedentary time is associated with lower cardiorespiratory fitness among children, adolescents, adults, and older adults. Furthermore, the negative effects of sedentary behavior may occur independently of physical activity, indicating that physically active individuals may still experience reduced fitness levels if they spend excessive amounts of time sitting. In conclusion, increasing physical activity and reducing sedentary behavior are essential strategies for improving VO₂max and cardiorespiratory fitness, thereby supporting long-term health and functional capacity.